2022
DOI: 10.1186/s12879-022-07081-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in L1 ORF of human papillomavirus in women with cervical cancer with and without human immunodeficiency virus in Botswana and Kenya

Abstract: Background The variation of human papillomavirus (HPV) genotypes shapes the risks of cervical cancer and these variations are not well defined in Africa. Nucleotide changes within the L1 gene, nucleotide variability, and phylogeny were explored in relation to HIV in samples from Botswana and Kenya. Methods A total of 98 HPV-positive cervical samples were sequenced to identify different HPV variants. Phylogenetic inferences were used to determine HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Also the proportion of other high-risk HPV genotypes (HPV-39, 45, −51, −52, −56, −68) was at 7-10% ( Figure 1 ). Indeed, HPV-45 seems to be frequently detected in women with cervical cancer compared to women with precancerous lesions ( 27 , 35 ). Other high-risk HPV genotypes (HPV-31 and HPV-33) were detected at low rates ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the proportion of other high-risk HPV genotypes (HPV-39, 45, −51, −52, −56, −68) was at 7-10% ( Figure 1 ). Indeed, HPV-45 seems to be frequently detected in women with cervical cancer compared to women with precancerous lesions ( 27 , 35 ). Other high-risk HPV genotypes (HPV-31 and HPV-33) were detected at low rates ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding HPV genotypes other than HPV-16 and/or HPV-18, the percentage of HPV-58 appears to be higher in HIV-positive people than HIV-negative subjects in Botswana ( 19 , 26 , 31 ), although these results are derived from different technical approaches, and therefore cannot be fully compared. Additionally, the most common HPV genotypes found in women with cervical cancer are HPV-45, −58 and −35 ( 27 , 35 ). This is confirmed by Clifford et al ( 37 ), where it has been shown that beside HPV-16, HPV-18, HPV-45 and HPV-58 were the more frequently genotypes detected in HIV-positive subjects with ICC compared with HIV-negative with ICC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nurses should have sound knowledge about cervical cancer so they can provide optimal care and information to patients. Most of the studies have been published on the evaluation of genetic/expression variation of different genes/pathways in cervical carcinogenesis [ 23 27 ]. Limited number of studies have been published with respect the cervical cancer and cervical cancer screening awareness among healthcare professionals [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Botswana and Kenya, Tawe et al showed that 83•7% of participants screened had high-risk (HR) HPV genotypes, while 16•3% had low-risk (LR) HPV genotypes (5). In a study involving 482 participants in Cameroun, Doh et al reported a prevalence rate of 13•4% among the population (6).…”
Section: Introductionmentioning
confidence: 99%